Dynamic Performance Modeling Analysis and Bench Testing of Electric Cylinder Steering System of Autonomous Rail Rapid Transit - Lei XIAO; Jing PENG; Peiyao ZHANG; Sheng ZHANG; Zhenbao LI; Xiaocong LIU; Wanlu JIANG; Kai LIU (机车电传动)
The autonomous rail rapid transit (ART) is powered by electric power but uses a hydraulic system to achieve steering function. If the electric drive electric cylinder can be used to realize the steering function, it will effectively save the installation space of the steering system, and can avoid the loss of energy in the conversion process, and achieve the purpose of energy saving and emission reduction. The continuously improving power weight ratio of the modern servo motor also created conditions for achieving this goal. In this paper, the mathematical model of the electric cylinder steering system of the ART was established firstly, and then the simulation model of the electric cylinder steering system in MATLAB/Simulink was established to simulate the dynamic performance of the electric cylinder steering system. Thereafter, according to the actual working conditions of the ART, the dynamic performance test bench of the electric cylinder steering system was built and used to test the dynamic performance of the electric cylinder steering system. Finally, the simulation data and the test data were compared. The comparative analysis showed that the simulation results were in good agreement with the test results, which proved that the mathematical model was accurate and also verified the feasibility of replacing the hydraulic cylinder steering system with the electric cylinder steering system.